Training on the Completion and Reporting of Lecturer Workload to Improve Academic Performance” - Ariyani , Rika (CV. Pustaka An Nur, 2025)
This training on the completion and reporting of lecturers’ workload was motivated by the limited understanding among some lecturers in managing, documenting, and reporting their Tri Dharma of Higher Education activities in accordance with existing regulations. Inaccuracies in completing and reporting the Lecturer Workload (BKD) often lead to delays in data verification and overall performance evaluation. This training aimed to improve lecturers’ understanding and skills in systematically and accurately completing and reporting their BKD in line with the latest guidelines. The participants consisted of 35 lecturers from various study programs at INISMA Jambi. The implementation methods included lectures, interactive discussions, BKD completion simulations, and technical assistance using an online reporting application. The results indicated a significant improvement in participants’ ability to understand the components of the Tri Dharma and to prepare BKD reports in accordance with the format set by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek). Overall, the training proved effective in enhancing accuracy, timeliness, and lecturers’ awareness of the importance of BKD reporting as an instrument for improving academic performance and professional development.